Result that last.. Teachers as agents of change - Dorn Linda, Soffos Carla (Ron Blome)
This videotape provides explicit guidance for implementing coachiiing conferences and literacy team meetings that occur whithin the natural context of the school day. Classroom teachers demostrate the important of school-embedded professional development that includes literacy team meetings for collborative problem-solviing around teaching and learniing issues and peer coaching and mentoring sessions around a specific learning goal.
Area-Documental
Keywords: Genero-Guías educativas